Studies of the expression of the Wiskott-Aldrich syndrome protein. - Stewart, D M (1996)
The Wiskott-Aldrich syndrome (WAS) is an X-linked disorder characterized by thrombocytopenia, eczema, disorders in cell-mediated and humoral immunity, and a proclivity to lymphoproliferative disease. The gene responsible encodes a 53-kD proline-rich protein of unknown function (WASP). We produced a FLAG-WASP fusion protein that was used to immunize mice and produce mAbs against WASP. Using monoclonal anti-WASP in Western immunoblots, we have determined that WASP is present in the cytoplasmic but not nuclear fraction of normal human peripheral blood mononuclear cells, in normal human platelets, in T lymphocytes, non-T lymphocytes, and monocytes. The protein is produced in the B cell immunoblastic cell line DS-1, in normal EBV-transformed B cell lines, and in HEL92.1.7, but is barely detectable in MOLT-4 and not detectable in K562. WASP was present in two of four EBV-transformed cell lines from WAS patients. Splenic tissue immunostaining was performed in two patients, and the results correlated with the results of the Western blots. Sequence analysis of WASP cDNA from two patients who produce WASP show mutations causing amino acid substitutions. These studies establish a foundation for further studies aimed at understanding the function of WASP.